محاضرات في مقیاس اضطرابات الشخصیة عند الراشد - أسماء براهیمي (جامعة محمد بوضياف -المسيلة, 2024)
الكلمات المفتاحية : إضطرابات الشخصية ، الراشد Key words : personality disorders . adult تتناول المطبوعة أهم إضطرابات الشخصية عند الراشد بالتفصيل ، بدءا بمفهوم البنية و هو المفهوم القاعدي لعلم النفس المرضي لتكوين شخصية من نمط معين ببعدها السوي أو المرضي ، مكانيزمات الدفاع ، العرض و المرض ، و تصنيفات الأعراض المريض و إحتياجاته . Summary The publication deals with the most important personality disorders in adults . in detail its started with the concept of psychological stricture it is the basic concept in psychopathology to form a character of certain type . in its normal or pathologicol dimension defense mechanisms . presentation and disease clasification of patient symptoms and needs .